Cytotoxic Activities of (Graptophyllum pictum (L.) Griff) Ethanolic Extract and Its Fractions on Human Colon Cancer Cell WiDr - Azizah Amin; Andayana Puspitasari Gani; Retno Murwanti (Majalah Obat Tradisional, 2020)
Colon cancer is the third most common cancer in the world. Treatments for colon cancer might cause major side effects, hence increase opportunities for the development of new cancer drugs. One of the plants that potential to develop as an anticancer agent is daun ungu (Graptophyllum pictum (L.) Griff). From previous studies, G.pictum had cytotoxic activity against several cancerous cell lines. Traditionally, G.pictum leaves have been used for hemorrhoid treatment. The purpose of this study was to determine the cytotoxic activity of G.pictum ethanolic extract and its fractions on human colon cancer WiDr cells and to elucidate the compounds contained in most active extracts/fractions. G.pictum was extracted using 70% ethanol and fractionated using n-hexane, chloroform, and ethyl acetate, respectively. The yield of the extract obtained was 18.9%. The yield of hexane, chloroform, ethyl acetate, and ethanol-water fractions were 1.07%, 2.93%, 10.26%, and 84.82%, respectively. The cytotoxic activity was carried out on WiDr cells using the MTT assay. Cytotoxic activity was determined based on IC50 values. IC50 value of extract, hexane, chloroform, ethyl acetate and ethanol-water fraction obtained on WiDr cells were 1527,58; 143,97; 507,19; 3538,67 and 3186,60 μg/mL. The hexane fraction containing terpenoids and phenolics showed the highest cytotoxic activities against WiDr colon cancer cells.